Investigasi Peningkatan Efisiensi Penggunaan Baja Pada Bangunan Beton Bertulang - Fikkri Ahmad (Asosiasi Riset Ilmu Teknik Indonesia, 2023)
Since its invention in the 19th century until today, reinforced concrete has become a leading construction material due to its qualities; it is a strong and durable building material that can be used in any form of architecture at an affordable and reasonable cost. Thus, humanity has abandoned traditional building materials (stone, earth, straw, lime, wood and hemp, etc.) to benefit from the many advantages of reinforced concrete (Yasser et al., 2013). However, this conversion comes at a cost; the environmental consequences are serious, cement is the third largest emitter of CO2 after cars and coal-fired power plants, and the same applies to steel, despite significant progress in recycling (Ranjitham et al., 2021).